Moléculas recombinantes miméticas do CA125 e de seu autoanticorpo antiidiotipo e implicações na resposta imune do câncer de ovário - Siquieroli, Ana Carolina Silva (2011)
Ovarian cancer is the most common gynecologic cancer in the developed world, which continues to kill more women than all other gynecological cancers combined. The absence of signs and symptoms coupled with lack of screening strategies contribute to the late diagnosis in most patients, resulting in low cure rates. The Phage Display (PD) technology allows the selection of peptides and proteins including antibodies with high affinity and specificity for multiple targets. The molecules characterized in this study are potential new tools in both clinical diagnosis and therapy of ovarian cancer, and provide additional information to the parameters of the ongoing clinical routine. Our phage display strategy produced successful mimetic peptides to specific ovarian tumor antigens, which were able to discriminate malignant tumors from the benign ovarian disease. These markers have significantly improved the diagnostic value of the CA125. Finally, we have also generated through PD recombinant Fab antibodies that specifically bind to the mimetic peptides and to ovarian tumor antigens, which may present potential immunotherapeutic role in the ovarian carcinoma treatment.